2015
DOI: 10.1111/ele.12526
|View full text |Cite
|
Sign up to set email alerts
|

From species distributions to meta‐communities

Abstract: The extent that biotic interactions and dispersal influence species ranges and diversity patterns across scales remains an open question. Answering this question requires framing an analysis on the frontier between species distribution modelling (SDM), which ignores biotic interactions and dispersal limitation, and community ecology, which provides specific predictions on community and meta-community structure and resulting diversity patterns such as species richness and functional diversity. Using both empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 42 publications
5
111
1
Order By: Relevance
“…This is in line with previous findings that co-occurrence patterns are highly scale-dependent (Araújo and Rozenfeld 2014) and also that the effects of local interspecific interactions vanish at coarser spatial scales (Thuiller et al 2015). We found that with increasingly coarser resolution, both the signals of positive and negative interactions became indiscernible by JSDMs, whereby the signal of negative interactions was more sensitive to scale.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous findings that co-occurrence patterns are highly scale-dependent (Araújo and Rozenfeld 2014) and also that the effects of local interspecific interactions vanish at coarser spatial scales (Thuiller et al 2015). We found that with increasingly coarser resolution, both the signals of positive and negative interactions became indiscernible by JSDMs, whereby the signal of negative interactions was more sensitive to scale.…”
Section: Discussionsupporting
confidence: 92%
“…This was advantageous in providing a balance between improved model performance (coarse resolution) (Thuiller et al, 2015) and representation of Fig. This was advantageous in providing a balance between improved model performance (coarse resolution) (Thuiller et al, 2015) and representation of Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Species distribution models (SDMs), on the other hand, fit environmental predictors to observed presence-absence or abundance, bypassing uncertainties in parameters (reviews presented in Elith & Leathwick, 2009;Merow et al, 2014;Ehrlen & Morris, 2015;Guillera-Arroita et al, 2015). Although the former is arguably more important for abundance than occurrence, and at smaller spatial scales (Boulangeat et al, 2012;Fordham et al, 2012;Araujo & Rozenfeld, 2014;Thuiller et al, 2015;Schweiger & Beierkuhnlein, 2016), migration is a first-order constraint on changing plant distributions at regional to continental scales. SDMs typically provide strong fits to observations and are relatively easy to implement.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they commonly ignore biotic interactions that strongly affect species composition [but see Thuiller et al . ()]. Moreover, niche models assume that species track changing climatic conditions instantaneously, disregarding time‐lags and indirect effects of climate change such as habitat changes and disturbance‐driven perturbations (Elith & Leathwick ).…”
Section: Introductionmentioning
confidence: 99%